A Method to Predict Water Recovery Rate in the Collection and Froth Zone of Flotation Systems - Maldonado-Saavedra, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
This paper describes a method to predict water recovery rate into and through the foam in a bubble column operating under different gas rates, froth depths, and frother types and concentrations. Three frothers were considered: Metil Isobutil Carbinol (MIBC), a proprietary blend of alcohols, aldehydes, and esters commercialized under the name PINNACLE® 9891, and a PGE-based Dow Froth 1012 (DF1012). The water rate entering into the froth (foam) layer from the bubbly (collection) zone was estimated as the water rate overflowing the column when operating at a thin stable foam layer, i.e., 0.5 cm. It was observed that the rate at which water entered into the froth phase could be modelled as a unique linear function of the gas holdup below the froth, regardless of the frother chemistry. This is a fundamental result not previously found in the literature that also facilitates the calculation of the froth zone water recovery for deeper froths. The water recovery in the froth was found to be an inverse logarithmic function of the average liquid residence time in the froth. Although the same trend was observed for the three frothers tested, they did not converge into a single function, which suggests that frother chemistry plays a role in determining froth structure and then needs to be incorporated when modeling water transport in the froth. Finally, the water overflow rate calculated as the product of the water rate into the froth and froth water recovery predicted the actual measured values fairly well. The water transport model here proposed provides a simple representation of the interactions between collection and froth zone and its relation to easily measure operating variables. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.